Pessimism of Modernity in the Short Stories by J.M.G Le Clezio: Genetic Structuralism Study - Dian Pratiwi; Reny Nur Rohmah; I Subandrio (Universitas Negeri Semarang, 2025)
La ronde et autres faits divers is collection of short stories explores the hars reality faced by marginalized potrayed by J.M.G. Le Clézio. This research will examine how the marginalized are represented and how the relation between characters is displayed through the narratives. This research uses a qualitative approach with a sociology perspective. The materials objects are three short stories titled Voleur O Voleur, Ariane, and Moloch with a formal object of its narrative structures. Data collection was carried out by documenting words, phrases, dialogues depicting the relation between hero(ine)s with other characters, then analyzing them using content analysis techniques adapted to the concept of genetic structuralism. The results of this research shows that modernization has many negative impacts on French society, such as demoralization, individualism, and environmental destruction. Le Clézio presents his worldview through his writing in which he describes the injustice and alineation experienced by hero(ine) who are trapped in modern society. The author employs realism to convey criticism and reveal the true reality, where the author feels pessimistic over the impacts of the modernization. Through its ambivalence, Le Clézio shows that no matter how hard individuals try to escape the shackles of modernization, they will still be part of the process itself.